2016
DOI: 10.1136/heartasia-2016-010789
|View full text |Cite
|
Sign up to set email alerts
|

Development of macaronic Hindi-English ‘Hinglish’ text message content for a coronary heart disease secondary prevention programme

Abstract: Background Coronary heart disease (CHD) is a leading cause of morbidity and mortality in India. Text message based prevention programs have demonstrated reduction in cardiovascular risk factors among patients with CHD in selected populations. Customisation is important as behaviour change is influenced by culture and linguistic context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Key activities covered included patient consultations, remote diagnosis, and follow-up through videoconferencing. Mobile phones were primarily used for treatment adherence reminders (text and Interactive Voice Response), appointment reminders, and behavior change messaging (n=8) [ 18 , 21 , 28 - 33 ]. Development process was described in 21 articles, 32 articles reported utility [ 16 - 25 , 30 , 31 , 34 - 57 ], and 20 articles reported user acceptability of the initiative [ 28 , 32 , 33 , 58 - 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Key activities covered included patient consultations, remote diagnosis, and follow-up through videoconferencing. Mobile phones were primarily used for treatment adherence reminders (text and Interactive Voice Response), appointment reminders, and behavior change messaging (n=8) [ 18 , 21 , 28 - 33 ]. Development process was described in 21 articles, 32 articles reported utility [ 16 - 25 , 30 , 31 , 34 - 57 ], and 20 articles reported user acceptability of the initiative [ 28 , 32 , 33 , 58 - 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mobile phones were primarily used for treatment adherence reminders (text and Interactive Voice Response), appointment reminders, and behavior change messaging (n=8) [ 18 , 21 , 28 - 33 ]. Development process was described in 21 articles, 32 articles reported utility [ 16 - 25 , 30 , 31 , 34 - 57 ], and 20 articles reported user acceptability of the initiative [ 28 , 32 , 33 , 58 - 74 ]. Other aspects explored were technology-related perception of the end users (n=13) [ 29 , 75 - 85 ], patient satisfaction (n=2) [ 86 , 87 ], assessment of health care professional needs, and challenges related to health service delivery using IT (n=2) [ 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence indicating that SMS is an acceptable and effective way to increase nutrition knowledge, promote positive diet-related behavior, and could encourage healthier food choices among students (11). For example, in the study of [48], the use of text messaging as an intervention to educate students on diet and coronary heart disease risk proved to have a positive impact on whole-grain consumption and high-density lipoprotein cholesterol. More than 90% of the study participants also indicated that a large proportion of SMS that they received were centered on reproductive and sexual health issues.…”
Section: Discussionmentioning
confidence: 99%
“…The team running these projects comprised of highly motivated researchers and academics with clinical and technical knowledge, which facilitated smooth delivery while keeping the overheads low. We also desired to deliver multiple similar trials varying by time zone, locations, and message customization [27]. …”
Section: Discussionmentioning
confidence: 99%